If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + 4x = -2x Solving -18 + 4x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -18 + 4x + 2x = -2x + 2x Combine like terms: 4x + 2x = 6x -18 + 6x = -2x + 2x Combine like terms: -2x + 2x = 0 -18 + 6x = 0 Add '18' to each side of the equation. -18 + 18 + 6x = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 6x = 0 + 18 6x = 0 + 18 Combine like terms: 0 + 18 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| -8x-9=39 | | -8x-9=29 | | y^2-4x^4=0 | | 6e^4x+13e^2x=28 | | -4y+1=2 | | B/7-11=7 | | 12+13=7x-7 | | -15=c-15 | | 8(-13)-3(-13-5)=4(-13)+4(-13+6) | | 2y-4=3y-9 | | 8-2b=-2/3(12b+6) | | y=+25 | | 13/15(x-3y-5z) | | 2(z-1)/2z-3-3(z+2)/2z-3-z-1/3-2z | | 1.72g-9=0.46 | | x^2-(5-i)x+6=0 | | 28=k+14 | | 2x+9x=-5 | | 5/7d=45 | | 1/8/1/3(2)=x | | 3+8x-6=6x+7 | | C/-10=-5 | | 5a+4b=20 | | 2Xsquared+9X=-5 | | 48-x+22+2-x= | | 4a=0.36 | | −3y+7+1 | | 5x+2x-4=38 | | 2(2x+3)-2=4(x+1) | | -18x+2=3x | | 2(4x-6)-8=8x-20 | | -x-3x-3=9 |